Interaction of amyloid and tau on cortical microstructure in cognitively unimpaired adults. Issue 1 (13th May 2021) - Vogt, Nicholas M.; Hunt, Jack F. V.; Adluru, Nagesh; Ma, Yue; Van Hulle, Carol A.; III, Douglas C. Dean; Kecskemeti, Steven R.; Chin, Nathaniel A.; Carlsson, Cynthia M.; Asthana, Sanjay; Johnson, Sterling C.; Kollmorgen, Gwendlyn; et al.
Abstract: Introduction: Neurite orientation dispersion and density imaging (NODDI), a multi‐compartment diffusion‐weighted imaging (DWI) model, may be useful for detecting early cortical microstructural alterations in Alzheimer's disease prior to cognitive impairment. Methods: Using neuroimaging (NODDI and T1‐weighted magnetic resonance imaging [MRI]) and cerebrospinal fluid (CSF) biomarker data (measured using Elecsys® CSF immunoassays) from 219 cognitively unimpaired participants, we tested the main and interactive effects of CSF amyloid beta (Aβ)42 /Aβ40 and phosphorylated tau (p‐tau) on cortical NODDI metrics and cortical thickness, controlling for age, sex, and apolipoprotein E ε4. Results: We observed a significant CSF Aβ42 /Aβ40 × p‐tau interaction on cortical neurite density index (NDI), but not orientation dispersion index or cortical thickness. The directionality of these interactive effects indicated: (1) among individuals with lower CSF p‐tau, greater amyloid burden was associated with higher cortical NDI; and (2) individuals with greater amyloid and p‐tau burden had lower cortical NDI, consistent with cortical neurodegenerative changes. Discussion: NDI is a particularly sensitive marker for early cortical changes that occur prior to gross atrophy or development of cognitive impairment.